Qualidade do cuidado pré-natal e nascimento prematuro - Melo, Emiliana Cristina (2015)
Current transversal study with puerperas residing in Maringá PR Brazil who took the pre-natal course and gave birth through the Brazilian National Health System (SUS) was conducted to analyze factors associated with pre-natal quality and factors associated with premature birth. Data were collected between October 2013 and February 2014 by interviews and analysis of the puerperas´ charts. Within a total of 576 puerperas, the sample took into account reliability interval at 95%, sample error at 0.025% and prevalence at 13% of premature birth plus 10% possible losses. Pre-natal quality was assessed according to three criteria: (1) Kessner´s Index which assessed pregnancy age at the start of the pre-natal course and the number of visits to the doctor during the period; (2) the number of laboratory tests for hemoglobin, syphilis and urine were added to Kessner´s Index, (3) the number of times that pregnancy age, womb height, cardiofetal heart beats, fetal presentation and blood pressure were taken plus the results of the former two calculations. Logistic regression (Prevalence Ratio PR, crude and adjusted) was undertaken to test the association of pre-natal care quality and premature birth and the association between the quality of pre-natal care and maternal circumstances. Hierarchized logistic regression was performed to analyze the following characteristics associated with premature birth: social, economic and demographic (Level 1, distal), pre-conception (Level 2, intermediary), pregnancy and quality of assistance in pregnancy (Level 3, proximal). Inadequate pre-natal care measured by Kessner´s Index predicts pre-mature birth (OR=3.79; IC=1.79;8.02). Maternal, obstetric and assistance predicting characteristics following Kessner´s Index were non-white skin color (OR=1.67; IC=1.11;2.51); multiparous (OR=2.18; IC=1.17;4.03); unplanned pregnancy (OR=2.06; IC=1.34;3.17) and mixed pre-natal course (OR=5,70; IC=2.93;11.09). Hierarchized statistical analysis showed that premature birth in the case of the above mentioned population is independent of the social, economic and demographical features of the pregnant women. The predictor role for those who already had a premature child is evident (OR=2.82; IC=1.37;5.80). Twin-birth was the proximal level strongly associated to premature birth, with a 12-fold increase (OR=12.92; IC=1.38;70.35), followed by hospitalization during pregnancy (OR=1.77; IC=1.07;2.93) and inadequate pre-natal care (OR=1.70; IC=1.04;2.80). Results show that pre-natal care must follow the minimum protocols by the Health Ministry, mainly the start of pre-natal attendance before the 16th week of conception and a sufficient number of visits to the doctor, so that pre-nature birth would be avoided. Colored and multiparae females and females with a non-planned pregnancy should be given special care by health professionals since they have a greater prevalence for inadequate pre-natal attendance. Decrease of prematurity may be controlled by adequate clinical attendance, guidelines and proper references to other doctors during pregnancy, with special emphasis to women with previous premature baby, twin pregnancy, women hospitalized during pregnancy and those who started after the 16th week of pregnancy. Results may help in the elaboration of strategies to reduce the frequency of premature births of women attended by the public health service with the above-mentioned characteristics.